Mesalamine-Induced Myocarditis - Olivier Merceron; Clement Bailly; Antoine Khalil; Florence Pontnau; Nadjib Hammoudi; Richard Dorent; Pierre-Louis Michel (Cardiology Research and Practice)
Nowadays mesalamine is a common treatment for Crohn's disease and hypersensitive reactions to this product have been reported. Yet there is limited information concerning mesalamine-induced myocarditis and its mechanism is not known. We described a case of mesalamine-induced myocarditis in Crohn's disease of the colon.